Energy Diplomacy and Strategic Realignment: Nigeria’s Foreign Policy Choices Amid the Iran–United States Conflict - Anthony C. Nwokolobia; Daniel Mevayerore Igbini (Universitas Medan Area, 2026)
This study examines Nigeria’s foreign policy choices in the context of energy diplomacy and strategic realignment amid the Iran–United States conflict. The research focuses on how geopolitical tensions, global energy market fluctuations, and historical alliances shape Nigeria’s diplomatic strategies and decision-making processes. Employing the historical research method with secondary sources only, the study critically reviews academic publications, policy documents, official statements, speeches, and credible media reports to trace the evolution of Nigeria’s foreign policy and energy diplomacy over time. Content analysis is used to systematically identify recurring themes and patterns, including energy security, national interest, strategic partnerships, and alignment with global powers. Findings reveal that Nigeria’s foreign policy is both reactive to international developments and proactive in protecting its economic and strategic interests. The study highlights the country’s pragmatic approach to balancing relationships with major powers while safeguarding its energy resources. Based on the findings, the study recommends that Nigeria strengthen multilateral energy diplomacy, enhance strategic foreign policy planning, and invest in continuous research to inform evidence-based decision-making. This research contributes to the understanding of how medium-sized oil-producing nations navigate complex international conflicts, offering insights into the intersection of energy security and foreign policy in a volatile global environment.